Cellular defense mechanisms against asbestos fibers - Barlow, Christy A.; Mossman, Brooke T. (Frontiers in Public Health, 2025)
Although inhalation of sufficient doses and dimensions of airborne asbestos dusts in an occupational setting can produce cancer in the lungs, pleura and peritoneum, tumors occur in <5–10% of exposed individuals, even among persons with considerable historical exposures. In this perspective, we review cell defense mechanisms that are involved in protective and adaptive responses to asbestos exposure. These adaptive responses are orchestrated through a multifaceted cellular program involving the concerted action of diverse stress response pathways, including antioxidant responses, DNA repair mechanisms, molecular mechanisms for intracellular signaling leading to proliferation, apoptosis, and inflammation, and cell cycle regulation. These cell defenses suggest that humans can adjust to moderate levels of stress or change without experiencing negative effects, implying the existence of a threshold dose. Likewise, reported no-observed adverse-effect levels (NOAELs) for various asbestos fiber types and asbestos-related cancers in experimental and epidemiological data further support the existence of a threshold dose and are discussed here.